An Investigation of the Design Potential of Thermochromic Home Textiles Used with Electric Heating Techniques. (11th October 2015) - Chen, Hung-Jen; Huang, Lan-Hui
Abstract : Thermochromic colorants have been developed since before the 1900s. There are a large number of patents in different applications of thermochromic textiles, but many innovations leave the field of aesthetic and functional textile design unexplored in the area of smart materials. This study aims to develop thermochromic home textiles that change colors and patterns by integrating thermochromic pigments and electric conductive yarns into textile structures. Stainless steel conductive yarns were sewed on textile substrates to enable heat generation to increase fabric temperature. The heat generation and temperature rise could be controlled by monitoring the voltage applied. The experiments of this study focused on analyzing electric resistance and heating properties of the conductive yarns and observing color changing time and color changing effects of the thermochromic textiles. By using the technique in this research, an image of "tai chi" was designed and implemented in a backlighting thermochromic fabric. It illustrates a range of opportunities for thermochromic textiles in new design research directions of Chinese calligraphy and traditional Chinese painting.